The Gnostic New Age : How a Countercultural Spirituality Revolutionized Religion from Antiquity to Today. - DeConick, April D. (Columbia University Press, 2016)
Gnosticism is a heretical tradition that revolutionized the practice of Christianity. Before Gnosticism emerged in the second century, passage to the afterlife required obedience to God and king. Gnosticism proposed that human beings were manifestations of the divine, unsettling the hierarchical foundations of the ancient world. Subversive and revolutionary, Gnostics taught that prayer and mediation could bring human beings into an ecstatic spiritual union with a transcendent deity. This mystical strain affected not just Christianity but many other religions, and it characterizes our understan.